Are there disparities in different domains of physical activity between school-aged migrant and non-migrant children and adolescents? Insights from Germany - Reimers, Anne Kerstin; Brzoska, Patrick; Niessner, Claudia; Schmidt, Steffen C.E.; Worth, Annette; Woll, Alexander (PLoS ONE, 2019)
BackgroundLarge proportions of the populations in many European countries, including Germany, are migrants. Migrant children and adolescents tend to be less physically active than their non-migrant peers. However, current research is limited as it does not sufficiently consider different domains of physical activity. Using a representative dataset, the present study examines the patterns of sports participation and other domains of physical activity among migrant and non-migrant children and adolescents residing in Germany.MethodsNationwide data from the Motorik-Modul (MoMo) Study is used. Five different domains of physical activity participation (sports clubs, outside of sports clubs, extra-curricular physical activity, physical activity, outdoor play and active commuting to school) were compared between children and adolescents with no, one-sided and two-sided migration background using logistic regression adjusted for demographic factors. Interaction terms were included in order to examine whether difference between the three groups differ by age and gender.ResultsInformation on n = 3,323 children and adolescents was available. As compared to non-migrants, children and adolescents with a two-sided migration background had a 40% (adjusted odds ratio [aOR] = 0.60, 95%-CI: 0.44-0.81), those with a one-sided migration background a 26% (aOR = 0.74, 95%-CI: 0.55-<1.00) lower chance of participating in sport club activities. In contrast, children and adolescents with a two-sided migration background were at 65% higher chance of participating in extra-curricular physical activity than nonmigrants (OR = 1.65, 95%-CI: 1.15-2.36).ConclusionThe study shows that differences in levels of physical activity between migrant and non-migrant children and adolescents are less pronounced than previous research has suggested. In particular, it reveals that migrants are only disadvantaged regarding participation in sports clubs whereas they fare better with respect to extra-curricular physical activity. Interventions should therefore address barriers migrant children and adolescents encounter in the access to sport clubs while maintaining their high level of extra-curricular physical activity.